Feasibility Study of a New Approach to Balance Job Demands and Resources - Annette Meng; Birgit Aust (Nordic Journal of Working Life Studies)
Childcare workers are faced with high job demands. The use of selection, optimization, and compensation strategies (SOC) may help reach a better balance between job demands and resources. We aimed to develop and evaluate the feasibility of a participatory intervention to increase the collective use of SOC strategies among childcare workers. Five childcare institutions participated in the development and evaluation of the intervention. Feasibility of the intervention was evaluated through interviews, observations, and a questionnaire survey. We transformed the SOC terminology into the more practical applicable terminology ‘PEX’: Prioritize tasks, Explore resources, and use of eXternal resources, and developed a dialogue tool. The PEX approach seems feasible to use in childcare institutions, and to have the potential to increase the collective use of SOC strategies and thereby improve employee well-being. Also, the study illustrates how important it is that feasibility studies allow for adjustments based on the active participation of employees.